113k views
5 votes
What is f(–3) for the function f(a) = –2a2 – 5a + 4?

User Nmc
by
5.0k points

2 Answers

1 vote
f(-3)=f(a)
-3=a

So you need to plug -3 into all the a's


f(a) = f( - 3) = - 2 ( - 3)^(2) - 5( - 3) + 4

= -2(9) - (-15) + 4
= -18 + 15 + 4
= -3 + 4
= 1

Answer:

When you plug input of -3 your output will be 1
User Giuseppe Ricupero
by
5.4k points
6 votes

Answer:

The value of f(-3) is 1.

Explanation:

Given expression,


f(a)=-2a^2-5a+4----------(1)

For finding the value of f(-3),

Put a = - 3 in equation (1),

We get,


f(-3)=-2(-3)^2-5(-3)+4


=-2(9)+15+4


=-18+19


=1

Hence, the value of f(-3) is 1 for the given function.

User Marcy
by
5.4k points